What works – reaching universal HIV testing: lessons from HPTN 071 (PopART) trial in Zambia. (17th July 2017) - Shanaube, Kwame; Schaap, Ab; Floyd, Sian; Phiri, Mwelwa; Griffith, Sam; Chaila, Joseph; Bock, Peter; Hayes, Richard; Fidler, Sarah; Ayles, Helen
Abstract : Objective: To determine the uptake of home-based HIV counselling and testing (HCT) in four HPTN 071 (PopART) trial communities (implementing a 'full' combination HIV prevention package that includes universal HIV testing and treatment) in Zambia. We also explore factors associated with uptake of HCT in these communities. Design: HPTN 071 (PopART) is a three-arm community-randomized trial in 12 communities in Zambia and nine communities in South Africa evaluating the impact of a combination HIV prevention package, including universal HIV testing and treatment, on HIV incidence. Methods: Using a door-to-door approach that includes systematically revisiting households, individuals were offered participation in the intervention, and verbal consent was obtained. Data were analysed for the first 18 months of the intervention, December 2013 to June 2015 for individuals 18 years and older. Results: Among 121 130 enumerated household members, 101 102 (83.5%) accepted the intervention. HCT uptake was 72.2% (66 894/92 612), similar by sex but varied across communities. HCT uptake was associated with younger age, sex, community, being symptomatic for TB and sexually transmitted infections and longer time since previous HIV test. Knowledge of HIV status due to the intervention increased by 36% overall and by 66% among HIV positive participants; the highest impact was among 18–24 years old. Conclusion: Overall acceptance of HIV-testing through offering a door-to-door-based combination HIV prevention package was 72.2%. The intervention increased knowledge of HIV status from ∼50 to ∼90%. However, challenges still remain and a one-off intervention is unlikely to be successful but will require repeated visits and multiple strategies.